Vocational Rehabilitation of American Indians with Alcohol Disorders. Research Dissemination Workshop Proceedings (Phoenix, Arizona, November 19, 1997) - Northern Arizona Univ., Flagstaff. American Indian Rehabilitation Research and Training Center; Sanderson, Priscilla Lansing; Gahungu, Athanase; Northern Arizona Univ., Flagstaff. American Indian Rehabilitation Research and Training Center ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
A workshop aimed to increase participant knowledge about how to improve vocational rehabilitation (VR) services for American Indians with alcohol disorders. Objectives included dissemination of results of a national research project; an overview of issues related to rehabilitation, alcohol abuse, and American Indian people; and specific suggestions for improving rehabilitation services for this population. This proceedings contains five papers and other materials. "Research on American Indians with Alcohol Abuse or Dependency" (Robert M. Schacht) reports on a survey of 31 treatment centers, 90 percent of which were culturally sensitive or used an explicitly Native treatment orientation. "Arizona VR Policies on Serving Clients with Alcohol Abuse or Dependency" (Valerie Lintz) clarifies relevant Arizona policies. "Screening Clients for Alcohol Problems" (Timothy C. Thomason) suggests screening procedures in the initial client interview and outlines features of 10 screening instruments. "American Indian Cultural Issues Regarding Alcohol and Alcoholism" (Candace Shelton) outlines general cultural principles for working with American Indians and discusses appropriate and inappropriate counselor behaviors. "VR Strategies for American Indians with Alcohol or Drug Abuse or Dependency" (Robert M. Schacht) discusses job performance, whether substance abuse or dependency is considered a disability, and specific VR counselor strategies. Appendices contain the Twelve Steps of Alcoholics Anonymous, Arizona VR policies related to substance dependency, a directory of 12 Arizona treatment programs with special services for American Indians, the workshop schedule, recommended readings, and diagnostic criteria for alcohol abuse and dependence. (SV)
Availability: Northern Arizona Univ., Inst. for Human Development, P.O. Box 5630, Flagstaff, AZ 86011; Tel: 520-523-4791.
Sponsoring Agency: National Inst. on Disability and Rehabilitation Research (ED/OSERS), Washington, DC.
Contract Number: H133B30068.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alcohol Abuse; Alcoholism; American Indian Culture; American Indians; Clinics; Counseling Services; Counseling Techniques; Counselor Client Relationship; Cultural Awareness; Disabilities; Public Policy; Rehabilitation Counseling; Screening Tests; Surveys; Vocational Rehabilitation; Workshops; Arizona; Collected Works, Proceedings; Guides, Non-Classroom.